Protective Effect of Arbidol Against Pulmonary Fibrosis and Sepsis in Mice - Li, Hailong; Liu, Rui; Zhang, Ruotong; Zhang, Shanshan; Wei, Yiying; Zhang, Liang; Zhou, Honggang; Yang, Cheng (Frontiers in Pharmacology, 2021)
From the perspective of epidemiology, viral immunology and current clinical research, pulmonary fibrosis may become one of the complications of patients with Coronavirus disease 2019 (COVID-19). Cytokine storm is an important cause of new coronavirus death. The purpose of this study was to explore the effects of antiviral drug arbidol on cytokine storm and pulmonary fibrosis. Here, we use a mouse model of bleomycin-induced pulmonary fibrosis and a mouse model of fecal dilution-induced sepsis to evaluate the effects of arbidol on pulmonary fibrosis and cytokine storm. The results showed that arbidol significantly reduced the area of pulmonary fibrosis and improved lung function (reduced inspiratory resistance, lung dynamic compliance and forced vital capacity increased). Treatment with arbidol promoted reduced sepsis severity 48 h after sepsis induction, based on weight, murine sepsis score and survival rate. Arbidol observably alleviates inflammatory infiltrates and injury in the lungs and liver. Finally, we also found that arbidol reduced serum levels of pro-inflammatory factors such as TNF-α and IL-6 induced by fecal dilution. In conclusion, our results indicate that arbidol can alleviate the severity of pulmonary fibrosis and sepsis, and provide some reference for the treatment of cytokine storm and sequelae of pulmonary fibrosis in patients with COVID-19.